Bahasa dan Identitas Kelompok dalam Pernyataan Tokoh Politik: Sebuah Studi Sosiolinguistik - Fadlilah, Afi; Utari, Rini; Iskandar, Denny (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This research aims to analyse the lingual forms of political figures' statements and their correlation to the speakers' identity from a sociolinguistic perspective. This research used a qualitative approach with descriptive data type. The object of this research is Megawati's statement in a live broadcast on the BKKBN Official YouTube account on 16 February 2023 in the event